Interval Training with Different Intensities in Overweight/Obese Adolescent Females - Abassi, Wissal; Ouerghi, Nejmeddine; Nikolaidis, Pantelis T.; Hill, Lee; Racil, Ghazi; Knechtle, Beat; Feki, Moncef; Bouassida, Anissa (International Journal of Sports Medicine, 2021)
To compare the effects of 12 weeks of high-intensity interval training (HIIT) versus moderate-intensity interval training (MIIT) on hematological and inflammatory markers in youth females, 38 overweight/obese females (16.4±1.0 yrs.) were randomly assigned to HIIT (2×6–8 repetitions of 30 s at 100–110% maximal aerobic speed (MAS), with 30 s active recovery between repetitions at 50% MAS; n=13), MIIT (2×6–8 repetitions of 30 s at 70–80% MAS, with 30 s active recovery between repetitions at 50% MAS; n=13), and a control group (CG, no intervention; n=12). Body composition, blood pressure, maximal heart rate, hematological and inflammatory markers (C-reactive protein [CRP], and erythrocyte sedimentation rate [ESR]) markers were assessed in all groups before and following the training program. Results revealed a significant (P<0.05) interaction effect for body composition, systolic blood pressure (SBP), MAS, maximal heart rate, and CRP. Within-group analyses for the HIIT and MIIT groups showed significant improvements in body mass (P=0.009 and P=0.025, respectively), BMI Z-score (P=0.011 and P=0.028, respectively), and MAS (P<0.001 and P=0.011, respectively). The HIIT program showed a significant decrease in body fat (P=0.002), waist circumference (P=0.002), maximal heart rate (P=0.003), SBP (P=0.001), and plasma CRP (P=0.004). In both groups, no signiﬁcant changes were observed in ESR and hematological markers after intervention. No variable changed in CG. HIIT was the effective method to manage cardiometabolic health and inflammatory disorders in obese youth.
Keywords: cardiovascular fitness; C-reactive protein; interval training; obesity